A gradient nanostructure generated in pure copper by platen friction sliding deformation. (May 2016) - Deng, S.Q.; Godfrey, A.; Liu, W.; Hansen, N.
Abstract: A modified friction sliding process with a large applied normal load has been used to develop a gradient nanostructure in Cu using only a short processing time. A quantitative characterization of the variation in microstructure and strength has been carried out by combined use of electron backscatter diffraction and hardness measurements, and the data used to estimate the effective strain profile resulting from the processing treatment. The affected deformation volume extends to a large depth of more than 1 mm, with a top surface hardness of 2.28 GPa, corresponding to a four-fold increase compared to the initial undeformed material. Graphical abstract: